2002
DOI: 10.1088/0305-4470/35/5/312
|View full text |Cite
|
Sign up to set email alerts
|

Casimir effect for scalar fields under Robin boundary conditions on plates

Abstract: Abstract. We study the Casimir effect for scalar fields with general curvature coupling subject to mixed boundary conditions (1 + β m n µ ∂ µ )ϕ = 0 at x = a m on one (m = 1) and two (m = 1, 2) parallel plates at a distance a ≡ a 2 − a 1 from each other. Making use of the generalized AbelPlana formula previously established by one of the authors [1], the Casimir energy densities are obtained as functions of β 1 and of β 1 ,β 2 ,a, respectively. In the case of two parallel plates, a decomposition of the total C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
288
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(315 citation statements)
references
References 34 publications
25
288
0
2
Order By: Relevance
“…This result (32) could also have been directly obtained by using the fact that, in the special case under consideration, the problem is conformally related to the corresponding one for Robin plates in Minkowski spacetime [15,16]. From this relation, it follows that…”
Section: Vacuum Expectation Value Of the Field Squaredmentioning
confidence: 67%
See 2 more Smart Citations
“…This result (32) could also have been directly obtained by using the fact that, in the special case under consideration, the problem is conformally related to the corresponding one for Robin plates in Minkowski spacetime [15,16]. From this relation, it follows that…”
Section: Vacuum Expectation Value Of the Field Squaredmentioning
confidence: 67%
“…In the discussion below we will assume that all zeros are real. In particular, this is the case for the conditions b j 0 (see [15]). The positive solutions of Eq.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…[27]). Hence, we conclude that the formulae given above for the core induced parts in the VEVs are valid in the case of the presence of bound states as well.…”
Section: Resultsmentioning
confidence: 99%
“…(1) (with the appropriate change of its parameters) and the BC from Eq. (2) describe the processes in acoustics [2], electrodynamics [3], plasma [4], scalar field theory [5][6][7][8], superconductivity [9][10][11][12] where the coefficient Λ is called the de Gennes distance [13], and others [14,15]. Nonexhaustive list of the relevant research efforts can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%